The importance of consumer based brand equity on consumer’s brand loyalty towards fast food restaurants in Perak - Yogeswari A/P Ramalingam (2011)
Strong brand equity has become a very important factor that influences consumer’s brand loyalty. Success in brand management arises from understanding and managing brand equity correctly to produce strong attributes that will influence consumers when making their choices. This thesis focuses on the importance of these dimensions (brand awareness, brand image and perceived quality) of customer-based brand equity on consumer’s brand loyalty. This is based on the assumption that all these dimensions of customer based-brand equity will have influence on consumer’s brand loyalty. However, this thesis aims to find out is there relationship between consumer’s brand loyalty towards these three dimensions (brand image, brand awareness and perceived quality) and also to find out which among these three dimension have appear to have the highest brand loyalty towards fast food restaurants in Perak. A structured questionnaire was constructed to provide answers to our research question. In this study, one hundred questionnaires were distributed to the customers of fast food restaurants based in Ipoh,Perak.The study surveyed three dimensions of consumer’s based brand equity namely brand awareness, brand image and perceived quality. Among the three dimensions, brand image appears to have the highest brand equity rating by consumers than the other dimensions. Although, the three dimension appear to have influence on consumer’s brand loyalty.